Comprehensive genomic and immunohistochemical profiles and outcomes of immunotherapy in patients with recurrent or advanced cervical cancer - Kim, Yoo-Na; Lee, Kyunglim; Park, Eunhyang; Park, Junsik; Lee, Yong Jae; Nam, Eun Ji; Kim, Sang Wun; Kim, Sunghoon; Kim, Young Tae; Lee, Jung-Yun (Frontiers in Oncology, 2023)
Purpose: This study aimed to investigate genomic and immunohistochemical (IHC) profiles and immunotherapy outcomes in patients with cervical cancer. Methods: Patients with recurrent cervical cancer who underwent tumor next-generation sequencing (NGS) with the TruSight Oncology 500 panel at Yonsei Cancer Center between June 2019 and February 2022, were identified. Patients who received treatment with checkpoint inhibitors during the same period were also identified. Clinical information, including histology, stage, human papillomavirus (HPV) genotype, IHCs profile, and therapy outcome, was reviewed. Results: We identified 115 patients treated for recurrent cervical cancer, including 74 patients who underwent tumor NGS. Most of these 74 patients were initially diagnosed with advanced stage (63.6%) and had squamous cell histology (52.7%), and high-risk HPV (76.9%). Based on IHC analysis, the programmed death-ligand 1 combined positive score (PD-L1 CPS) was higher in patients with squamous cell carcinoma (SCC) than in those with adeno or mucinous types (P=0.020). HER2 receptor expression of 2+ and 3+ were identified in 5 and 1 patients, respectively, and significantly varied based on histology (p=0.002). Among the 74 patients, single nucleotide variants (SNVs) and copy number variations (CNVs) were identified in 60 (81.1%) and 13 patients (17.6%), respectively. The most common SNVs were PIK3CA, TP53, STK11, FAT1, and FBXW7 mutations. Mutations in PIK3CA, with two hotspot mutations, were frequently observed in patients with SCC histology, whereas mutations in TP53 were frequently observed in patients with non-SCC histology. Additionally, variations in FAT1 were exclusively identified in patients with SCC histology. Mutations in homologous recombination repair-associated genes were identified in 18 patients (24.3%). The most frequent CNV alteration was CCNE1 amplification. Moreover, among the 36 patients who underwent NGS and received immunotherapy, the tumor mutational burden and microsatellite instability were significantly correlated with immunotherapy duration. During this timeframe, 73 patients received pembrolizumab monotherapy, among whom a small portion showed a durable response. Conclusion: Comprehensive genomic and IHC profiling may help identify potential candidates for targeted immunotherapy in patients with cervical cancer.